ANALISIS RITUAL TRADISI TUANG MINYAK PADA WANITA HAMIL ETNIS MELAYU DI DESA BERLIMANG KABUPATEN SAMBAS - Iwan Ramadhan; Sana Sana; Imran Imran; Agus Sikwan (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2024)
This research aims to find out how the series of initial, core and final processions of the traditional ritual of pouring oil on ethnic Malay pregnant women in Berlimang Village, Teluk Keramat District, Sambas Regency. This traditional ritual of pouring oil is a tradition of the Malay ethnic community which is carried out by women who are pregnant for the first time when they are seven months pregnant with the aim of praying that the pregnant woman and her unborn baby will be given health and safety until the birth process. The method used is qualitative descriptive. The data collection techniques used are data reduction, data presentation, and drawing conclusions. The informants consisted of four people, namely, one person as the main informant, and three people as supporting informants. The results of this research show that the initial ritual process of pouring oil includes: making ratahan, then bathing to ward off evil in order to avoid disaster. The core processes of the traditional ritual of pouring oil include: belinggang, massaging the stomach, bepappas, all of which are carried out by dukun beranak. The final process of the traditional ritual of pouring oil includes: a joint prayer led by the village Labai, eating besaprah with invited guests and giving tampas to the dukun beranak as a form of thanks. Apart from that, the traditional ritual procession of pouring oil also contains values, meanings and functions implicit in it so that it can be used as a guide for life in society.